Severe necrotizing methicillin-sensitive Staphylococcus aureuspneumonia, septic shock, and multiorgan failure in a young man withclassical dengue fever: A case report - Vijayan, Lexy (Indian Journal of Case Reports, 2026)
Dengue fever is one of the most common mosquito-borne viral illnesses worldwide. Although most cases are selflimiting, concomitant bacterial infections may result in severe complications and increased mortality. A 32-year-old previously healthy male presented with a 7-day history of rash over the right side of the neck extending to the occipital region, 4 days of fever, vomiting, malaise, headache, neck swelling with restricted neck movements, and 1 day of cough and shortness of breath. Evaluation revealed neck cellulitis, bilateral pneumonia, thrombocytopenia, acute kidney injury, myocarditis, hepatic dysfunction, and methicillin-sensitive Staphylococcus aureus (MSSA) bacteremia. Dengue immunoglobulin M was positive. Despite initial broad-spectrum antibiotic therapy, the patient developed progressive necrotizing pneumonia requiring mechanical ventilation. Following escalation to targeted antimicrobial therapy together with adjunctive therapy, significant clinical improvement was observed, and the patient was discharged in stable condition. Severe bacterial coinfection should be considered in dengue patients with atypical clinical deterioration. Early recognition and prompt treatment of MSSA-associated necrotizing pneumonia may be life-saving.